2004
DOI: 10.1093/ps/83.7.1218
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Inactivation of Salmonella and Listeria Monocytogenes in Ground Chicken Thigh/Leg Meat and Skin

Abstract: Thermal inactivation D and z values of Salmonella and Listeria monocytogenes were obtained for chicken thigh and leg meat and skin. The D values of Salmonella at 55 to 70 degrees C were 43.33 to 0.07 min in the meat and 43.76 to 0.09 min in the skin. The D values of L. monocytogenes at 55 to 70 degrees C were 38.94 to 0.04 min in the meat and 34.05 to 0.05 min in the skin. The z value of Salmonella was 5.34 degrees C in the meat and 5.56 degrees C in the skin. The z value of L. monocytogenes was 5.08 degrees C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 25 publications
4
33
1
1
Order By: Relevance
“…couldn't be detected in chicken frankfurters ( Table 1). Absence of Salmonellae in heat-treated poultry meat products (such as frankfurter) may be attributed to the thermal treatment used in processing procedures was effective for killing these sensitive bacteria (Murphy et al, 2004). In addition, spices which include parsley, black pepper, garlic, nutmeg, and mustard, among others are used in chicken frankfurters to impart flavor and enhance aroma of the finished product; these spices are added for their antimicrobial effects (Brown, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…couldn't be detected in chicken frankfurters ( Table 1). Absence of Salmonellae in heat-treated poultry meat products (such as frankfurter) may be attributed to the thermal treatment used in processing procedures was effective for killing these sensitive bacteria (Murphy et al, 2004). In addition, spices which include parsley, black pepper, garlic, nutmeg, and mustard, among others are used in chicken frankfurters to impart flavor and enhance aroma of the finished product; these spices are added for their antimicrobial effects (Brown, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Earlier reports have shown that high level of fat (>20%) provides a protective effect for bacterial pathogens subjected to heat treatment (Fain et al 1991;Murphy et al 2004). This protective effect could be a consequence of reduced water activity in milk medium (Senhaji and Loncin 1977).…”
Section: Resultsmentioning
confidence: 99%
“…Since ready-to-eat (RTE) meat and poultry deli products can be consumed without further cooking, these products should be free of non-spore-forming pathogens following the industrial thermal process. However, they can become contaminated before packaging in the final retail wrap and thus pose a safety threat for consumers (8,9). Viral contamination of RTE and prepared foods most frequently comes from poor hand-washing practices of food handlers after toilet use.…”
mentioning
confidence: 99%